The Generalization of the Exterior Square of a Bieberbach Group with Symmetric Point Group - Idrus, Nor’ashiqin Mohd.; Ting, Tan Yee; Masri, Rohaidah; Sarmin, Nor Haniza; Hassim, Hazzirah Izzati Mat (Journal of Informatics and Mathematical Sciences, 2016)
The exterior square is a homological functor originated in the homotopy theory, while Bieberbach groups with symmetric point group are torsion free crystallographic groups. In this paper, the generalization of the exterior square of a Bieberbach group with symmetric point group is constructed up to finite dimension.